SUSTAINABLE GROUNDWATER MANAGEMENT FOR UTILIZATION IN AGRICULTURAL PROJECTS: AL-SAQI ALTERNATIVE WATER PROJECT – KARBALA, IRAQ - Mahmood, Rafal Ghassan; Ahmed, Sally Hussein; Aziz, Omar Gheni (ANTIS PUBLISHER, 2025)
Objective: Groundwater represents the most important source for sustaining agriculture and maintaining socio-economic development, especially in arid and semi-arid regions such as Iraq’s western desert, as surface water is scarce. Method: Al-Saqi Alternative Water Project in Karbala province represents one of the most important projects, which depends on GW to cultivate different types of corps, has adopted the latest agricultural technologies and smart fertilization systems under the supervision of specialized companies, so that 3 main scenarios were put forward in order to get the optimal exploitation for the whole area of project (35000 dunums) with no leading to GW scarcity. Results: First scenario includes planting only wheat, proved to be a sustainable scenario, whereas the second one involved cultivating many summer and winter crops (each for the whole area), which showed markable risk. In the last scenario, it was assumed that a mix of summer crops is planted together evenly and so on for Winter crops, which eventually showed partial success. Novelty: The outcomes of this study emphasised that crop type selection and land-use plan play a vital role in maintaining groundwater sustainability.